2006
DOI: 10.1242/jeb.01957
|View full text |Cite
|
Sign up to set email alerts
|

Induced airflow in flying insects I. A theoretical model of the induced flow

Abstract: SUMMARY A strong induced flow structure envelops the body of insects and birds during flight. This flow influences many physiological processes including delivery of odor and mechanical stimuli to the sensory organs, as well as mass flow processes including heat loss and gas exchange in flying animals. With recent advances in near-field aerodynamics of insect and bird flight, it is now possible to determine how wing kinematics affects induced flow over their body. In this paper, I develop a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…U ind was probably greater, by some unmeasured amount, than the induced velocity at the wing (Ellington, 1984;Sane, 2006). We were unable to measure U ind at the wing because the wings and body, and reflection of laser light, obscured near-field flow patterns.…”
Section: Digital Particle Image Velocimetrymentioning
confidence: 94%
“…U ind was probably greater, by some unmeasured amount, than the induced velocity at the wing (Ellington, 1984;Sane, 2006). We were unable to measure U ind at the wing because the wings and body, and reflection of laser light, obscured near-field flow patterns.…”
Section: Digital Particle Image Velocimetrymentioning
confidence: 94%
“…We propose here an analytical method based on lifting line blade models. Sane [13] presented a lifting line blade model for hovering flapping wings; however, the model relied on empirical experimental data, and hence measurements are still required for the calculation. Leishman [14, ch.…”
Section: Non-uniform Downwash Velocity Effectmentioning
confidence: 99%
“…Although this formula was originally developed for rotors with finite number of blades, Sane [13] showed that it can be used within the context of flapping flight, suggesting a value of 2 for N b to simulate a complete wing cycle and a value of 1 for a single up-or downstroke. For a hovering case, l is the ratio of the induced downwash velocity to the wing tip velocity rsif.royalsocietypublishing.org J. R. Soc.…”
Section: Tip Loss Effectmentioning
confidence: 99%
See 2 more Smart Citations